2005
DOI: 10.1681/asn.2005020167
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Gαq-Coupled Signaling Pathways in Glomerular Podocytes Promotes Renal Injury

Abstract: The glomerular podocyte plays a key role in maintaining the integrity of the glomerular filtration barrier. This function may be regulated by activation of cell surface G protein-coupled receptors (GPCR). Studies suggest that podocytes express GPCR that are implicated in the pathogenesis of glomerular diseases. Common to these GPCR systems is activation of phospholipase C through the Gq ␣-subunit (G␣q). For investigating the role of G␣q-coupled signaling pathways in promoting renal injury in podocytes, a const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 66 publications
5
46
0
Order By: Relevance
“…In addition, intraperitoneal injection could lead to tolerance, which prevents the reproduction of MCD model in mice [13]. Wang et al [14] showed that a single epidermal injection of PAN (0.5 mg/g) in mice can generate excess urine protein, thus reproducing the classic rat disease model in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraperitoneal injection could lead to tolerance, which prevents the reproduction of MCD model in mice [13]. Wang et al [14] showed that a single epidermal injection of PAN (0.5 mg/g) in mice can generate excess urine protein, thus reproducing the classic rat disease model in mice.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 The factors that initiate COX-2 upregulation in podocytes have only recently been investigated. Spurney et al 28 showed that Gq-dependent signaling induces COX-2 expression in cultured podocytes, which was associated with increased PGE 2 synthesis. Our previous work showed that both mechanical stretch and PGE 2 induce COX-2 expression in cultured mouse podocytes.…”
Section: Discussionmentioning
confidence: 99%
“…We used male mice because female mice are relatively resistant. Previous studies successfully induced PAN nephrosis in mice after a high dosage (500 mg/kg subcutaneously), 34 after a high-cholesterol diet, 35 or with multiple doses (20 mg/kg subcutaneously or 90 mg/kg intraperitoneally). 36,37 We found that PAN led to an increase in UAE associated with foot process effacement and a reduction in podocin and ZO-1 mRNA expression.…”
Section: Discussionmentioning
confidence: 99%